Leadership in Halal Business Sector: Bibliometric Analysis and A Roadmap for Future Research - Fitriani, Fitriani; Wahab, Abd.; Hendratmi, Achsania (Universitas Gadjah Mada, 2025)
Introduction/Main Objectives: This study investigates leadership's role in the halal business sector, focusing on Islamic principles such as justice, integrity, and ethical decision-making. Leadership is crucial for business growth and addressing ethical and operational challenges in the expanding halal industry. This topic is significant due to the rising global demand for halal products and the need for leadership to ensure compliance with Islamic standards and sustain competitiveness. Background Problems: The halal sector faces standardization discrepancies, workforce development, and market competitiveness. This research asks: What are the trends, gaps, and future directions in leadership research within halal enterprises? Novelty: This study is the first to apply bibliometric analysis to leadership in halal enterprises, reviewing research from 1999 to 2024. Previous studies lacked exploration of leadership's role in fostering innovation, sustainability, and compliance. Research Methods: Bibliometric analysis of 60 Scopus-indexed publications using R-biblioshiny, Excel, and VOSviewer examines trends, collaborations, and gaps, complemented by content analysis. Finding/Results: Ethical leadership, strategic management, and innovation enhance halal businesses' competitiveness and compliance. Gaps highlight the need for interdisciplinary collaboration and leadership framework exploration. Conclusion: Leadership is essential for ethical challenges, sustainable growth, and global competitiveness, as well as for integrating ethics, innovation, and strategic management for halal industry success.